Eco-Friendly Sol-Gel Synthesis of Silver Nanoparticles using Morinda citrifolia Leaf Extract and PVP: Structural, Morphological and Antibacterial Properties - Kiranda Dinata; Shinta Wulan Asih; Lita Rahmasari (Jurusan Fisika FMIPA Universitas Andalas, 2026)
Silver nanoparticles (AgNPs) have strong potential as antibacterial agents, with effectiveness highly influenced by particle-size stability. This study synthesized AgNPs via a green sol-gel method using noni (Morinda citrifolia) leaf extract as a natural reducing agent and polyvinylpyrrolidone (PVP) as a capping agent. PVP concentrations of 0.5, 1.0, and 1.5 g were mixed with 25 mL noni extract and 25 mL double-distilled water. Characterization using UV–vis, XRD, FE-SEM/EDX, and FTIR showed decreasing UV–vis absorption peaks of 433, 412, 368 nm with increasing PVP content. XRD confirmed a face-centered cubic (FCC) crystal structure with >80% similarity to standard Ag patterns. FE-SEM/EDX indicated the presence of Ag, C, and O elements, and particle sizes remained stable at 16.8, 18.8, and 18.4 nm. The 0.5 g PVP sample produced the smallest particles and showed dominant O–H and C–H functional groups. It exhibited the strongest antibacterial activity, with inhibition zones of 12.5 mm (E. coli) and 12.0 mm (S. aureus). These results demonstrate that eco-friendly sol-gel-synthesized AgNPs using noni leaf extract and PVP exhibit promising antibacterial activity, positioning them as potential candidates for further development as antibacterial materials.